Ferramentas digitais no processo de reinvenção das bibliotecas escolares durante a pandemia - Filgueiras, Joelma da Silva (Brasil, 2021)
It aims to discuss how the digital tools contributed to the reinvention process of school libraries from the pandemic context. It highlights that the pandemic caused by Covid- 19, led to the social isolation and closure of various sectors to contain the virus, including libraries that, to offer information services, made use of digital tools that were indispensable for the continuity of activities. It assumes as research theme the digital tools, problematizes in the sense of understanding how libraries reconfigured themselves to meet their users at the time of the pandemic, and which tools were used to offer the services. It starts from the need to know how the digital tools can contribute to the process of reinvention of school libraries in the context of the Covid-19 pandemic, exposing the theoretical basis in five sections: digital technologies of information and communication, school library, the librarian professional, information service in school library and digital tools, was based on, Côrte and Bandeira (2011), Araújo and Vilaça (2016), Fernandes (2019), Paletta (2019), Voltoline (2019), Cunha and Fioravante (2020). It points out the methodological path from the characterization of the research, as to its nature, applied and exploratory. It highlights the application of the bibliographical method as procedure and case study and as data collection technique the questionnaire that was prepared in the online modality with the support of the digital tool Google Forms. It points out that the research universe involves the school libraries of the city of Manaus/Amazonas, composed of a random sample of 10 libraries, being seven municipal schools (SEMED), two of the state network (SEDUC) and one of the private educational network. It indicates that the research subjects were librarians from Seduc, Semed and Private network. It indicates that for data tabulation were adopted technological resources with support from the Google Forms tool, Office Microsoft Excel and Word. It points out the qualitative-quantitative approach and content analysis technique based on the method of Bardin (2016). The result pointed out that the digital tools were part of the reinvention process of school libraries during the pandemic, however, this evolution happened in an unstable way due to the public schools not being prepared with electronic resources available for all libraries. It ends by highlighting the expectation of the research contribution for the use of other digital tools that can streamline the services to users and cooperate with the improvement of library services and engagement between librarians and users.